THE TRANSFORMATIVE IMPACT OF AI ON BUSINESS IN UZBEKISTAN - J.B.Gayratov (Journal of new century innovations, 2024)
This article delves into the transformative impact of Artificial Intelligence (AI) on businesses in Uzbekistan, exploring the multifaceted changes in operational paradigms, decision-making processes, customer experiences, and innovation. Through the lens of streamlined operations, enhanced decision-making, and personalized customer interactions, we examine the positive influence of AI across diverse sectors. The article also addresses the challenges associated with AI adoption, such as the demand for a skilled workforce and concerns related to data privacy and job displacement. The study concludes by highlighting the strategic opportunities that AI presents for economic growth and job creation, positioning Uzbekistan as a dynamic player in the global business landscape. This comprehensive analysis underscores the need for a balanced approach, fostering innovation while addressing challenges to ensure sustainable and inclusive development in the era of AI.